The Effect of Principal Leadership and Work Discipline on Teacher Performance - Mirzon Daheri; Fitri Meliani; Freddrik Tiagita Putra; Nanda Saputra; Zida Syarifah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
The main task of a teacher is to educate, teach, guide, direct, train, assess, and evaluate students. The school principal should make a policy to qualify teachers, include the demands placed on teachers so that teachers are able to improve their performance, and apply good work discipline, so that teacher performance increases to the fullest. The purpose of conducting this research is to find out the influence of the principal's leadership and work discipline on teacher performance. Using a quantitative approach with the help of IBM SPSS version 23, this study tested the validity and reliability of the research instruments. While the respondents in the study were 95 respondents, using the census method by taking the entire population as a sample. Collecting data in research using a questionnaire. This study shows that the principal's leadership variable (X1) has an influence on teacher performance (Y1) seen in testing the T-test hypothesis where Tcount>Ttable (2.225 > 1.986) and a significant level of less than 0.05, namely (0.029<0.05), on the work discipline variable (X2) there is an influence on teacher performance, it is known based on the results of the t-test, namely Tcount>Ttable (5,567 > 1.986) and a significant level of less than 0.05 (0.000 <0.05), the variable principal's leadership and work discipline has a simultaneous influence on teacher performance, based on the F test, namely Fcount (35.394) > Ftable (3.09), with a significant level of less than 0.05, namely (0.000 <0.05).